Shape‐Controlled 3D Periodic Metal Nanostructures Fabricated via Nanowelding. Issue 6 (14th December 2017) - Zhao, Zhi‐Jun; Shin, Sang‐Ho; Choi, Dae‐Geun; Park, Sang‐Hu; Jeong, Jun‐Ho
Abstract: A novel method for fabricating 3D metallic nanostructures to be used in polarized color filters based on nanoimprint lithography, electron‐beam evaporation, and nanowelding is proposed. The shape of the nanostructures can be controlled by adjusting the temperature for the nanowelding process. Ag nanowires deposited on polymer patterns are accumulated by the nanowelding process to build up diverse 3D nanostructures. The morphologies of the fabricated 3D nanostructures are analyzed using scanning electron microscopy, atomic force microscopy, and focused ion beam; the heating temperature is varied from 90 to 130 °C in steps of 10 °C. In order to analyze the recrystallization phenomenon after welding, transmission electron microscopy is utilized. The 3D metallic nanostructure has different morphologies and optical properties corresponding to welding temperature conditions and accumulated layer thicknesses. Based on preliminary experimental results, the process parameters are optimized and a polarized color filter is fabricated. Optical characteristics of the filter are evaluated using polarizer and spectrometer. Through this work, it is shown that the proposed method is an effective way to realize various 3D metallic nanostructures for special optical properties, therefore the method based on nanowelding can be utilized in fabrication of functional metamaterials, optical filters, biosensors, and others. Abstract : A new method for fabricating 3D metal nanostructures based on nanoimprint lithography, electron‐beam evaporation, and nanowelding is proposed. This method allows for the shape of the nanostructures to be controlled by adjusting the temperature for the nanowelding process.